Comparison of Economical Analysis of Wood And Fiberglass Vessels In Randuboto Village, Gresik Regency, East Java - Rizky Chandra Ariesta; Mohammad Sholichan Arif; Hutami Putri Puspitasari (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2018)
Randuboto village is a region with great potential of fisheries, with most of the community's livelihood concentrating on marine produce. Commodities produced are shrimp, milkfish and fish. To develop the results and get the economic value of the catch, it is necessary to do adequate facilities and facilities analysis. The facilities and facilities are fiber vessels. In determining the business analysis, some analysis is needed to get optimal results. This study discusses the economic analysis of 5 GT fish vessels with wood and fiber materials in Desa Randuboto Gresik which aim to know the investment cost. These costs include the development of fiber vessels, the value comparison in terms of maintenance costs, the amount of investment incurred for the stage of development and the magnitude of the profit to be recovered. Based on the result of the analysis, the value of NPV is Rp. 115.563.937 for fish vessels with wood materials and Rp. 131.683.082,-  for fish vessels with fiber materials during 5 years. The results of this analysis indicate that this business is feasible to run.